The influence of illness duration before diagnosis on clinical characteristics and outcome in human brucellosis - Bosilkovski, Mile; Siskova, Dijana; Spasovska, Katerina; Vidinic, Ivan; Dimzova, Marija (SAGE Publications, 2019)
Our study assesses the influence of illness duration before establishing the diagnosis of brucellosis and initiating therapy on patients' main clinical characteristics and outcome in an endemic area. The medical files of 297 patients with brucellosis were retrospectively analysed. They were divided into four groups according to illness duration before initiating therapy: <10 days; 11-30 days; 31-90 days; and >90 days. There were significant differences in the occurrences of fever (P = 0.019), focal forms (P = 0.026), spondylitis (P = 0.034) and therapeutic failures (P = 0.006) between the groups. Duration of >30 days before treatment initiation is responsible for more serious clinical presentation and outcome, whereas illness duration of >90 days further worsens the clinical progression in human brucellosis.